2015
DOI: 10.1242/jeb.128751
|View full text |Cite
|
Sign up to set email alerts
|

Auditory modulation of wind-elicited walking behavior in the cricket, Gryllus bimaculatus

Abstract: Animals flexibly change their locomotion triggered by an identical stimulus depending on the environmental context and behavioral state. This indicates that additional sensory inputs in different modality from the stimulus triggering the escape response affect the neuronal circuit governing that behavior. However, how the spatio-temporal relationships between these two stimuli effect a behavioral change remains unknown. We studied this question, using crickets, which respond to a short air-puff by oriented wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(49 citation statements)
references
References 48 publications
6
42
1
Order By: Relevance
“…This results in a mean stimulus velocity measured at the cercus of 0.36 m/s (standard error 0.06, n = 15). With this regime we never observed walking sequences, escape runs or jumps, which often occur at higher stimulus intensities (Gras and Hörner, 1992; Stevenson et al, 2005; Oe and Ogawa, 2013; Fukutomi et al, 2015). …”
Section: Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…This results in a mean stimulus velocity measured at the cercus of 0.36 m/s (standard error 0.06, n = 15). With this regime we never observed walking sequences, escape runs or jumps, which often occur at higher stimulus intensities (Gras and Hörner, 1992; Stevenson et al, 2005; Oe and Ogawa, 2013; Fukutomi et al, 2015). …”
Section: Methodsmentioning
confidence: 79%
“…Furthermore, the intensity of the AS was set to below that required to elicit escape walking jumps or runs (cf. Gras and Hörner, 1992; Oe and Ogawa, 2013; Fukutomi et al, 2015), and aggression was always evaluated 10 min after experiencing these stimuli. Notably, prior stimulation with a washed male, or female antennae was not effective (Figure 3), indicating that male cuticular pheromones (cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also employed DeepHL to analyze context-dependent modulation of escape behavior in field crickets, Gryllus bimaculatus . Fukutomi et al 31 , 32 revealed that an acoustic stimulus at high frequency (>10 kHz) preceding an air puff alters crickets’ moving direction in wind-elicited escape behavior, suggesting that the crickets recognize the high-frequency sound as the echolocation signal of bats and change their behaviors in the presence of predators. Here, we adopted DeepHL to compare two groups of escape movement: prestimulated and control (no sound).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the cricket exhibits an escape response to a short air-puff detected by cerci, which is considered as a defensive behaviour against lunging predators such as spider 24 , 25 . In a previous study, we explored the auditory impact on the wind-elicited escape behaviour and reported that a preceding acoustic stimulus of a 10-kHz pure tone that evoked no response alone modulated moving direction and response threshold of wind-elicited walking 26 . This fact revealed that a cross-modal interaction between auditory and cercal sensory systems caused behavioural changes in escape strategy, suggesting that crickets perceived the acoustic signals and interpreted them as acoustic contexts.…”
Section: Introductionmentioning
confidence: 99%